FAKTOR KESULITAN BELAJAR SISWA PADA PEMBELAJARAN MENULIS CERPEN KELAS IX - Wa Ode Husniati; Sri Suryana Dinar; La Tike; Muhammad Rifa'ie (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to analyze the factors of students' learning difficulties in learning to write short stories in class IX of SMP Negeri 1 Kusambi, West Muna Regency. The research method used is a qualitative method with data collection techniques in the form of questionnaires, interviews, and documentation. The subjects of the study were class IX who had difficulty in writing short stories. The instruments used to collect data were questionnaires and interviews. Based on the results of the study with reference to several internal factors, it shows that the cognitive aspect is the main obstacle, where around 74.7% of students have difficulty understanding the structure of short stories (for example, plot and setting) and 78.1% of students admit to having difficulty in mastering vocabulary. In addition, affective factors such as low learning motivation (68.9%) and lack of self-confidence (64.4%) also contribute to the difficulty of writing short stories. Meanwhile, the psychomotor aspect, which includes writing skills and motor skills in writing, also shows obstacles, although the percentage is relatively lower when compared to cognitive and effective factors. External factors from the external side, family environmental support, although still low (inadequate learning facilities at home around 59.8%) also influence the process of learning to write short stories. The social environment that does not support literacy activities in the surrounding area is also an obstacle. In the school environment, less interesting learning methods (71.2% of students) and unsupportive school facilities (65.5% of students) further worsen the condition. Furthermore, teachers who provide less writing practice (77.0% of students) indicate that opportunities for structured writing practice are still minimal.